Magnitude of slowing gastric emptying by glucagon‐like peptide‐1 receptor agonists determines the amelioration of postprandial glucose excursion in Japanese patients with type 2 diabetes. Issue 2 (25th July 2019) - Suganuma, Yumi; Shimizu, Tatsunori; Sato, Takehiro; Morii, Tsukasa; Fujita, Hiroki; Harada Sassa, Mariko; Yamada, Yuichiro
Abstract: Aims/Introduction: Pharmacological levels of glucagon‐like peptide‐1 (GLP‐1) can decelerate gastric emptying (GE) and reduce postprandial glucose levels. Most previous studies have used liquid meals to evaluate GE. We evaluated the effects of GLP‐1 receptor agonists (GLP‐1 RAs) on GE and postprandial glucose excursion in Japanese type 2 diabetes mellitus patients using a combination of solid and liquid meals. Materials and Methods: In this single‐center, prospective, open‐label study, nine healthy individuals and 17 patients with type 2 diabetes mellitus consumed a 460‐kcal combination of a solid and liquid meal labeled with 13 C‐acetic acid. GE was measured from t  = 0 to 150 min in a continuous 13 C breath test. Eight participants with type 2 diabetes mellitus were administered GLP‐1 RAs, and we examined the relationship between GE and blood glucose excursion. Results: There were no differences in the average GE coefficient (GEC) and lag time between the healthy and type 2 diabetes mellitus groups. However, the type 2 diabetes mellitus group showed larger GEC variations ( P <  0.05). The coefficient of variation of R‐R intervals was a significant predictor of GEC in type 2 diabetes mellitus patients ( P  <   0.01). The short‐acting GLP‐1 RA reduced the GEC at 1 month ( P  =   0.012), whereas the long‐acting GLP‐1 RA did not significantly change the GEC after treatment. A positive relationship was observed between postprandial glucose excursion from T 0 min to T 60 min and the GEC ( r 2  = 0.75; P  <   0.01). Conclusions: The reduction in GE rate by the administration of GLP‐1 RAs can predict the improvement in postprandial glucose excursion in type 2 diabetes mellitus patients. Abstract : The purpose of this research was to evaluate the effect of glucagon‐like peptide‐1 receptor agonists on gastric emptying and postprandial glucose excursion in Japanese patients with type 2 diabetes mellitus using both liquid and solid meals. We revealed that the reduction in gastric emptying by the administration of glucagon‐like peptide‐1 receptor agonists can predict the improvement in postprandial glucose excursion in type 2 diabetes mellitus patients, using a combination of liquid and solid meals, and a continuous 13C breath test.